Pengaruh Kenaikan PDRB Harga Konstan Dan Pengeluaran Perkapita Terhadap Persentase Penduduk Miskin Kota Pekanbaru - Herman Herman (Eko dan Bisnis: Riau Economic and Business Review, 2025)
This study aims to determine the increase in GRDP and per capita expenditure on the poverty percentage in Pekanbaru City. The data source obtained is primary data. The data analysis technique used is multiple linear regression analysis, the tool used is SPSS 25. The results of the study indicate that GRDP and per capita expenditure have a significant effect on the poverty percentage in Pekanbaru City. The Adjusted R Square value of 0.987 means that 98.7% of the variation in changes in the percentage of the poor population can be explained by two independent variables in the model, namely: GRDP and per capita expenditure. In other words, almost all variations in the rise and fall of the poverty rate in Pekanbaru City can be explained by the regression model used. The remaining 1.3% is explained by other factors outside the model, such as education level, population, inflation and employment opportunities